2020
DOI: 10.30699/fhi.v9i1.216
|View full text |Cite
|
Sign up to set email alerts
|

Information Needs of Women with Breast Cancer: A Review of the Literature

Abstract: Introduction: Breast cancer is one of the most common cancers and a serious concern for women's health. Providing sufficient information to these patients increases the level of their participation and improves the quality of their care. Therefore, given the high survival rate of this cancer, it is necessary to understand their information needs. The purpose of this study was to evaluate the information needs of women with breast cancer.Material and Methods: The study is a systematic review of the literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Even if patients are satisfied with the care or information they have received, they may seek additional information from other sources. Arabic-speaking cultures have little data on breast and colorectal cancer patients’ digital trends, preferred sources of information, and online information seeking [ 6 ]. Alnaim in 2019 [ 7 ] examined the quality of breast cancer information on Arabic websites and found that while many exist, few are moderated by experts, the majority provide poor quality information, and only two-thirds provide completely correct information.…”
Section: Introductionmentioning
confidence: 99%
“…Even if patients are satisfied with the care or information they have received, they may seek additional information from other sources. Arabic-speaking cultures have little data on breast and colorectal cancer patients’ digital trends, preferred sources of information, and online information seeking [ 6 ]. Alnaim in 2019 [ 7 ] examined the quality of breast cancer information on Arabic websites and found that while many exist, few are moderated by experts, the majority provide poor quality information, and only two-thirds provide completely correct information.…”
Section: Introductionmentioning
confidence: 99%
“…Patient empowerment and realistic expectations regarding their conditions will assist them to cope well during the survivorship [ 8 , 12 ]. Despite the substantial studies into cancer information needs and sources that have been conducted [ 11 – 13 , 15 17 ], the studies have methodological limitations such as a homogeneous and unrepresentative population, small sample size, being exploratory in nature, or have low response rates [ 8 – 13 , 16 ]. Additionally, cancer patients’ information-seeking patterns are influenced by clinical and socio-demographic factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, to determine the main theme for an education-based app, the main themes for training must first be identified; then a context must be created [37]. Studies similar to ours mostly used the following themes: analyzing side effects, lifestyles, and social activities [38,39]. In order to design our app user interface to better communicate with patients, we sought out experts in user experience and software in these fields.…”
Section: Discussionmentioning
confidence: 99%